1974
DOI: 10.1111/j.1471-4159.1974.tb04405.x
|View full text |Cite
|
Sign up to set email alerts
|

A STUDY OF SELECTED CATECHOLAMINE METABOLIZING ENZYMES: A COMPARISON OF DEPRESSIVE SUICIDES AND ALCOHOLIC SUICIDES WITH CONTROLS1

Abstract: The regional distributions of monamine oxidase (MAO) (EC 1.4.3.4), catechol-0methyltransferase (COMT) (EC 2.1.1.6), tyrosine hydroxylase (TH) (EC 1.14.3.2), and dopamine-Phydroxylase (DBH) (EC 1.14.2.1) have been examined in human brains obtained at autopsy from persons who died of natural causes (controls), and from persons who committed suicide and were further categorized as suffering from affective disorder (depression) or from alcoholism. Post mortem animal studies showed no changes in M A 0 or COMT activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

1975
1975
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(26 citation statements)
references
References 28 publications
2
24
0
Order By: Relevance
“…Although few studies have focussed specifically on the striatum, in vitro data are indicative of significant age related increases in MAO-B enzyme activity (Grote et al, 1974;Robinson et al, 1977;Fowler et al, 1980;Saura et al, 1997). Equivocal findings (Domino et al, 1973) can be explained by small sample size and lack of differentiation between the two MAO isoforms.…”
Section: (Ii) Dopamine Metabolismmentioning
confidence: 89%
See 1 more Smart Citation
“…Although few studies have focussed specifically on the striatum, in vitro data are indicative of significant age related increases in MAO-B enzyme activity (Grote et al, 1974;Robinson et al, 1977;Fowler et al, 1980;Saura et al, 1997). Equivocal findings (Domino et al, 1973) can be explained by small sample size and lack of differentiation between the two MAO isoforms.…”
Section: (Ii) Dopamine Metabolismmentioning
confidence: 89%
“…The decline was exponential, with the most substantial losses occurring between the ages of 5-25 yrs. Some studies have also reported equivocal or negative results, but as they employed non-standardized dissection methodology (Robinson et al, 1977), or the use of older sample groups which could not be expected to explore the effects of loss in early adult life (Grote et al, 1974;Mackay et al, 1978a), this may explain inconsistencies in findings. The predominant limitation of studies of this type is the extreme sensitivity of TH to pre-and post-mortem conditions, estimations of enzyme activity being particularly affected by the interval between death and freezing of tissue (McGeer et al, 1971(McGeer et al, , 1976.…”
Section: (I) Biosynthetic Enzymesmentioning
confidence: 91%
“…The measurement of DOPAL will therefore contribute to a more accurate estimation of premortem levels of DA in postmortem human brain. In addition, because the enzymes involved in metabolism of DOPAL (aldehyde reductase, aldehyde dehydrogenase, and catechol-O-methyltransferase) either are in very low amounts (9) or are extraneuronal (10)(11)(12), DOPAL may be an index of the intraneuronal metabolism of newly formed DA (13).…”
Section: Introductionmentioning
confidence: 99%
“…However, substantial variability in absolute levels of platelet MAO activity has been noted in alcoholic and control populations [95,100], and MAO activity was also found to fluctuate significantly after cessation of alcohol intake by the alcoholic [95,99], pos sibly due to changes in platelet production. As a result, platelet MAO activity is not always found to be lower in alcoholics than controls [101], and is not a reliable identifier of alcoholic individuals. This conclusion is…”
Section: Ac Activity After Chronic Ethanol Treatmentmentioning
confidence: 99%